IMPLEMENTASI KEBIJAKAN PENGGUNAAN SISTEM INFORMASI DAN REKAPITULASI (SIREKAP) PADA PEMILIHAN KEPALA DAERAH SERENTAK TAHUN 2020 DI PROVINSI PAPUA - Agusta Maniagasi; Nur Aedah (Universitas Cenderawasih, 2022)
This study aims to analyze the Implementation of the General Election Commission (KPU) Policy regarding the Use of Sistem Informasi dan Rekapitulasi (SIREKAP) in the 2020 Simultaneous Regional Head Elections in Papua Province. Therefore, in this study, there are 3 main study focuses, firstly analyzing the description of the Implementation of the SIREKAP Policy in the 2020 Simultaneous Regional Head Elections in Papua Province. Second, analyze the supporting factors and inhibiting factors for the Implementation of the SIREKAP Policy in the 2020 Simultaneous Regional Head Elections in Papua Province. Third, analyze the efforts made to optimize the application of SIREKAP in post-conflict local elections. The research method used is descriptive qualitative. The research location is in Papua Province. The informant determination technique was selected purposively. The data collection used includes in-depth interviews, observation, and documentation. Data analysis techniques include the stages of data reduction, data presentation, data interpretation, and conclusion. The results of the study show that firstly, the implementation of the SIREKAP Policy in the 2020 Simultaneous Regional Head Elections in Papua Province from the aspect of interest, types of benefits, degree of change, the position of policymakers, executors, and resources used are by the objectives of implementing and holding transparent Pilkada and accountable because the presence of this SIREKAP facilitates the recapitulation process which can be accessed by the public so that it can build public trust in the implementation of regional elections. Even in the implementation stage, there were several obstacles encountered, both in the managerial aspects of operating the application, along with the technical problems in the field. Second, the determinant factors that support or hinder the Implementation of the SIREKAP Policy in the 2020 Simultaneous Regional Head Elections in Papua Province are the quality of human resources, Availability of the Internet Network, geographical conditions of the region, electricity network, and the use of Android Hangphones to operate applications. Third, the efforts made are to increase the level of availability of facilities and infrastructure to support the implementation of regional elections, especially for the application of SIREKAP. Then, make technical guidance and training activities for operators who will be placed in remote areas to be able to operate the SIREKAP application and as a pioneer in socializing this to the general public, so that when the next general election is held, regardless of whether it is a national election or a head election If the area wants to use SIREKAP, it will run optimally, not only in urban areas but in all areas in Papua.